Dependency of tablet among higher institution students in Kota Kinabalu / Mahathir Mohamad - Mohamad, Mahathir (2016)
In this globalization era, internet and computer technology are commonly known in many countries. In this paper, it will be focused on smartphones and tablets in perspective of the usage and demand. According to (Garber, 2012), new and better ways to interact with computing and communications technology had been introduced by researchers in order to make the consumers can do their daily activity easier, as well as more satisfying, engaging, and effective. "This allows users to apply technology to things you do in a very natural way," said Microsoft Surface director Somanna Palacanda. In addition, this study choose the tablet computer as the mechanism that consumers are commonly depended on. A tablet is a "device with a touchscreen interface, screen sizes ranging from 5 inches to 12 inches, color displays, Wi-Fi or 3G internet connectivity, and advanced mobile operating systems such as Apple iOS, Google Android, Windows 7 or BlackBerry" (Perrin, 2011 ).